The role of innovation in promoting digital financial inclusion -Lessons learned for Algeria through international experiences- - Lamraoui, salim (Journal of Research in Finance and Accounting, 2023)
This research aims to study the role of innovation in promoting digital financial inclusion by reading and drawing lessons learned for Algeria from some international experiences. In order to achieve the objectives of this research, the descriptive approach was relied upon by describing the variables of the study (innovation and digital financial inclusion), as well as the analytical approach to analyze its international reality, and An analytical study was also conducted for Algeria, Morocco, and Qatar. This research reached a number of results, the most important of which is: the use of digital financial services in Algeria is still low, although digital financial inclusion represents one of the main development goals of the country. Therefore, the research recommends the need to introduce a national strategy to drive innovation and digital transformation, and to establish financial technology incubators and projects.